Spirituality and religiosity in children, adolescents and their families in a vulnerable context: a scoping review - Marcela Teixeira de Souza; Layane Cristina Araújo; Alexandre Ernesto Silva; Liana Amorim Corrêa Trotte; Elaine Cristina Rodrigues Gesteira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to map evidence in the literature on the spirituality and religiosity of children, adolescents and their families in social vulnerability. Methods: this is a scoping review based on the JBI methodology, with the search without delimiting the time period, in English, Portuguese and Spanish, in the Virtual Health Library, PubMed, Embase, Cochrane Library, Scopus and Web of Science databases. Results: twenty-two studies were identified. The most studied population were adolescents, followed by children and their families. Regarding the setting, the context of vulnerability related to the low socioeconomic level experienced by these populations was highlighted. Furthermore, spirituality and religiosity were considered important for coping, social support, purpose and strength. Conclusion: there is an influence of spirituality and religiosity in the lives of children, adolescents and families, being a protective factor and a source of comfort, playing essential tools for living in context.